2019
DOI: 10.1021/acs.jpca.9b04568
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Effects: A Signature of J- and H-Aggregate of Carbon Nanodots in Polar Solvents

Abstract: The secret behind excitation-dependent/-independent photoluminescence of carbon nanodots (CDs) is not yet revealed completely. To address this issue, a detailed investigation on solvent polarity-dependent optical properties of citric acid–urea co-derived nitrogen-doped carbon nanodots (NCDs) was carried out. The interpretation on UV–visible spectral data reveals the presence of H-aggregates formed through hydrogen bonding. In addition, dipole–dipole interaction-mediated J-aggregates are clearly evident. The br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 41 publications
(130 reference statements)
1
11
0
Order By: Relevance
“…The π-stacking effect has been investigated in several molecules, analyzing solvent type, concentration, and time, among other variables [ 62 , 63 , 64 ]. Additionally, UV-Vis spectroscopy is one of the characterization techniques for identifying the presence of π-stacking [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The π-stacking effect has been investigated in several molecules, analyzing solvent type, concentration, and time, among other variables [ 62 , 63 , 64 ]. Additionally, UV-Vis spectroscopy is one of the characterization techniques for identifying the presence of π-stacking [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…This effect in Poly(Ani-AMPS) is produced by the inter- or intra-chain or both interactions among the anilinium cations, AMPS anion, and solvent. The equilibrium forces between the AMPS anion and anilinium cation (van der Waals forces, electrostatic repulsion, steric hindrance) allow the interaction and the final conformation, too [ 62 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that the size of these aggregates strongly depends on the concentration and that the maximum emission wavelength changes as the effect of the interaction with different solvents. A systematic investigation of the effect of nine polar solvents on the CA/U-CD absorption, emission, and lifetimes was performed by Anjali Devi et al The complex trends in the CA/U-CD optical features were explained with the self-assembly of the fluorophores into different coexisting structures, i.e., H-aggregates, J-aggregates, and combinations of the two, whose presence was also supported by TEM characterization. , Moreover, in the work of Bhuyan et al, it is shown how the reversible formation of aggregates from water to acetone goes in parallel with the blue emission suppression in favor of the green emission enhancement, reflecting the fluorescence resonance energy transfer (FRET)-mediated energy migration from the blue fluorophores to the green fluorophores inside the aggregate . Finally, Yao et al performed the microwave-assisted irradiation of citric acid and urea, achieving isolation by means of reversed phase C18 column chromatography of the fluorophore 5-oxopyrrolidine-3-carboxylic acid (OPCA) .…”
Section: Ca-cd Classesmentioning
confidence: 99%
“…For example, many molecules identified among the unpurified CA-CD mixtures form aggregates, slowing down the purification process. On the other hand, these aggregates could correspond to the CA-CDs themselves, as pointed out in several studies; thus, dialysis would not be the best option for their purification. , Beside dialysis, chromatography techniques provide a useful approach for understanding the composition of the raw CDs. Silica column chromatography, C18 reverse phase chromatography, , gel permeation chromatography, , size-exclusion chromatography, and ion exchange chromatography were exploited for the purification and/or characterization of the fluorophores for various CA-CD systems.…”
Section: General Aspects Of Ca-cdsmentioning
confidence: 99%
“…On the other hand, a study on the effect of surrounding media, namely, solvent effect, revealed additional photophysical characteristics of the CNDs . Recent reports on the solvatochromic response of CNDs revealed important emission parameters. …”
Section: Introductionmentioning
confidence: 99%